Penguatan Integritas Kepala Sekolah Dalam Mewujudkan Mutu SDM Di Sekolah Berbasis Islam Terpadu - Nasution, Faisal Hakim; Mukhtar; Kasful Anwar; Mahmud, Mahmud; Asrulla (Al-Riwayah : Jurnal Kependidikan, 2024)
Islamic education in its early development has had an advantage because of its own characteristics, namely being comprehensive with the aim of encouraging children to pour out all their abilities. The goals of Islamic education are derived from religious goals and worldly goals. Changes in the current era of globalization seem to require a proactive and anticipatory response from the world of education, especially in Islamic education. Human resources as the key to implementing change need to consider these conditions in order to improve the quality of education through continuous improvement. In educational management, one important area is related to human resources involved in the education process, whether it is educators such as teachers or educational staff such as administrative staff. The intensity of the educational world in relation to humans can be seen as an important difference between educational institutions and other organizations. The existence of high-quality human resources is very important for the progress of a madrasah. Integrated Islamic-based schools with adequate facilities and complete facilities, supported by the capabilities of madrasah resources as leaders in Islamic educational institutions, are obliged to carry out improvements to the available human resources, both teaching and non-teaching staff, in order to have quality capabilities